Jenny Thompson's Turn at 50 m of Her Gold Medal 100 m Race at the 1999 Pan Pacific Championships in Sydney - Rushall, B. S.
Video pictures (30 frames) and the appropriate technical/ biomechanical explanations for Jenny Thompson's Turn at 50 m of Her Gold Medal 100 m Race at the 1999 Pan Pacific Championships in Sydney. Jenny Thompson's turn is technically correct and efficient. This sequence should be used to demonstrate good crawl stroke turning technique.